Are They Well Situated? Spatial Analysis of Privately Owned Public Space, Manhattan, New York City. (May 2015) - Yoon, Heeyeun; Srinivasan, Sumeeta
In this article, we attempt to examine how privately owned public spaces through incentive zoning have played out as a means to generate public spaces, as part of improving spatial equity in Manhattan, New York City. Using spatial statistical analyses, we find that the inclusion of privately owned public spaces reduces overall average distance to the nearest public space from both working and living population, and helps to balance the distribution of the public spaces throughout the city, by covering the locations where publicly owned public spaces are sparse. More importantly, the location of privately owned public spaces closely aligns with potential demand from the working and tourist population, though not from the resident population. We extend the findings to policy, suggesting that allocation of privately owned public space should be implemented comprehensively rather than discretely, as well as in relationship to publicly owned public spaces, to sharpen their role in achieving fair distribution of public spaces throughout the city.